Pengaruh Motivasi, Disiplin Kerja, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan Blue Sky Hotel di Kota Balikpapan - Nita Julita; Syahril Hasan; Tutik Yuliani (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Human resources are the main asset of a company, making their presence crucial to support the organization's success. Therefore, companies must give greater attention to employees to ensure optimal job satisfaction. This study aims to examine the influence of Motivation, Work Discipline, and Work Environment on Employee Job Satisfaction at Blue Sky Hotel Balikpapan. The research adopts a quantitative approach using data collection techniques based on the Likert scale. A total of 74 employees from Blue Sky Hotel Balikpapan participated as respondents. Data analysis was conducted using the SmartPLS method, while data collection was carried out through questionnaires designed based on the Likert scale to assess employees' perceptions of the variables of motivation, work discipline, and work environment. The results of the study indicate that the motivation variable has a significant effect on employee job satisfaction at Blue Sky Hotel Balikpapan. Similarly, the work discipline variable significantly influences employee job satisfaction, and the work environment variable also significantly affects employee job satisfaction at Blue Sky Hotel Balikpapan.